Analysis on the hotspot characteristics of bird diversity distribution along the continental coastline of China - Hou, Peng; Bai, Junjun; Chen, Yan; Hou, Jing; Zhao, Jiajun; Ma, Yutiao; Zhai, Jun (Frontiers in Marine Science, 2022)
Global climate change and disturbances from human activities lead to habitat loss and changes in habitat quality, resulting in a reduction in biodiversity. The continental coastline of China distributes some cities with highly developed economies and coastal wetlands with rich biodiversity, and both economic development and biodiversity conservation are important topics. In order to clarify the spatial distribution of bird biodiversity in coastal areas, based on the MaxEnt model and GIS spatial analysis, the distribution data of 488 species of birds and 15 environmental variables were used to simulate the suitable distribution areas of birds, and to analyze the spatial distribution and hotspots of bird biodiversity in coastal areas. The main findings of this study are as follows. (1) A total of 488 species in 249 genera of 21 orders and 81 families of birds were involved in the modeling of coastal areas. The main environmental factors affecting the potential distribution of birds in general are: land use, monthly mean diurnal temperature range, and precipitation of the driest month. (2) High value areas of bird richness are distributed in different locations in the four sea areas: In the Bohai Rim region, they are mainly distributed in the Liaohe Estuary Wetland in Liaoning Province, the vicinity of the Yongdingxin River and Haihe River in Tianjin, the eastern part of Tianjin, and the Yellow River and Yellow River Delta Wetland in Shandong Province; In the coastal area of the Yellow Sea, they are primarily found in Kunyu Mountain National Nature Reserve, Laoshan Provincial Nature Reserve in Shandong Province, and Yancheng Wetland Rare Birds National Nature Reserve in Jiangsu Province; In the coastal areas of the East China Sea, they are mainly found at the mouth of the Yangtze River, at the national nature reserve of Dongtan birds on Chongming Island, along the southeastern coast of Zhejiang Province, near the Min River and along the coast of Quanzhou in Fujian Province; In the coastal areas of the South China Sea, they are mainly distributed in the Pearl River Delta wetlands of Guangdong Province, the southeastern coastal areas of the Guangdong-Hong Kong-Macao Greater Bay Area, and the Shiwanda Mountain National Nature Reserve in Guangxi Province. (3) The spatial trends in the distribution of hotspots of birds of national priority protection in coastal areas are generally consistent, but more concentrated than the distribution of all birds. (4) After the high-value areas of bird richness were superimposed with protected areas, it was found that the intersecting area accounted for a small proportion of the protected area, and many areas near the inland had low bird richness. Finally, the findings provide references for bird biodiversity conservation and planning in coastal areas.